Maithili in Medieval Nepal : A Historical Apprisal - Das, Basudevlal (Academic Voices: A Multidisciplinary Journal, 2014)
Nepal is a multi-linguistic nation. Maithili is one of the major languages of Nepal. This is spoken as a mother-tongue in eastern Tarai of Nepal. Historically speaking, the development of Maithili language took place in medieval period, where the two dynasties i.e. the Karnatas of Mithila and the Senas of Makawanpur had played major roles. Maithili expanded towards Kathmandu valley also. There are many manuscripts written in Maithili preserved in National Archive, Kathmandu. Even now, in the devotional songs sang by the aged persons in Kathmandu valley, there are many Maithili words found. Describing the importance of Maithili language in medieval period, this article may be a historical background for the people engaged in policy making and the language movement. Academic Voices, Vol. 3, No. 1, 2013, Pages 1-3 DOI: http://dx.doi.org/10.3126/av.v3i1.9704